Functional characterization of 2 news variants in the APOB gene - Alves, A.C. (2018)
Project grant FCT_PTDC/SAU-GMG/101874/2008; Ana Catarina Alves was funded by FCT SFRH/BD/27990/2006 and FCT_PTDC/SAU-GMG/101874/2008.